THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE AND ENVIRONMENTAL DISCLOSURE ON PROFITABILITY WITH FIRM SIZE AS MODERATING EFFECT (STUDY ON LISTED MINING COMPANY IN INDONESIA STOCK EXCHANGE YEAR 2017 2019) - Sahril, Fathin Adlia; Kamal, Maulana (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The economy moves away from polluting activities and towards cleaner production processes. Corresponding to this, companies are required not only to have high profitability but also to concern with environmental issues. It is expected that larger companies are able to generate more profits and to concern themselves with environmental issue. The purpose of this research is to investigate the influences of environmental performance and environmental disclosure on profitability with firm size as the moderating variable of that relationship. A sample of the listed mining companies of IDX was collected from 2017 to 2019 for hypothesis testing using a multiple regression analysis. The findings indicate that environmental performance and environmental disclosure were positively associated with profitability and firm size moderates this relationship.